Literary merit as a resource for human growth: the use of social networks for psychotherapeutic purposes - Chimpen-Lopez, Carlos; Moral, Manuel; Sevilla-Vallejo, Santiago (Journal of Poetry Therapy, 2023)
Narration is a tool to organize experience into a coherent vision that explains our identity. According to Paul Ricoeur, fictional characters and real people's identities are made out of the use of discourse. The tradition of narrative therapy states the importance of the use of letters, notes, and certificates to strengthen the alternative stories that are co-built with the person in the sessions. The digital format makes it easy not only to send but also to share such documents with a wider community. The so-called counter-documents are those writings that do not focus on problems but on the actions performed by people despite the problem and that contribute to the construction of so-called alternative stories. This article reflects on the use of these writings with literary merit for psychotherapy and also claims the need for psychotherapy to be updated and adapted to the current digital cultural context.
Keywords: literary merit; narrative therapy; poetry; letters; digital documents; social net; archives of resistance; Emerging; Scopus